2021
DOI: 10.1136/bmjopen-2021-057708
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinant factors of mental health problems among healthcare professionals during COVID-19 pandemic in southern Ethiopia: multicentre cross-sectional study

Abstract: ObjectiveTo assess the prevalence of depression, anxiety and stress and its determinant factors during COVID-19 pandemic among healthcare professionals in southern Ethiopia.DesignMulti-centre cross-sectional study.Setting and study periodRandomly selected public hospitals in Sidama, southern Ethiopia between 25 September 2020 and 25 October 2020.Participants387 healthcare professionals were randomly selected.Outcome measuresPrevalence and determinant factors of depression, anxiety and stress was assessed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(72 citation statements)
references
References 59 publications
3
61
1
Order By: Relevance
“…Most studies reviewed directly assessed the prevalence of depression, anxiety, Stress, insomnia, and PTSD in HCWs. Common causes of anxiety, fear, or psychological distress that health professionals reported were: lack of access to PPEs and other equipment, being exposed to COVID-19 at work and taking the infection home to their families, uncertainties that their organization will support/take care of their personal and family needs if they developed an infection, long working hours, death of colleagues, lack of social support, stigmatization, high rates of transmission and poor income [34][35][36][37][38][39][40][41][42][43][44][45]. The prevalence of mental health symptoms exhibited great variations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most studies reviewed directly assessed the prevalence of depression, anxiety, Stress, insomnia, and PTSD in HCWs. Common causes of anxiety, fear, or psychological distress that health professionals reported were: lack of access to PPEs and other equipment, being exposed to COVID-19 at work and taking the infection home to their families, uncertainties that their organization will support/take care of their personal and family needs if they developed an infection, long working hours, death of colleagues, lack of social support, stigmatization, high rates of transmission and poor income [34][35][36][37][38][39][40][41][42][43][44][45]. The prevalence of mental health symptoms exhibited great variations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most of the studies reviewed directly assessed the prevalence of depression, anxiety, stress, insomnia, and PTSD on HCWs. Common causes of anxiety, fear or psychological distress that health professionals reported were: lack of access to PPEs and other equipment, being exposed to COVID-19 at work, and taking the infection home to their families, uncertainties that their organisation will support/take care of their personal and family needs if they developed infection, long working hours, death of colleagues, lack of social support, stigmatization, high rates of transmission and poor income [34][35][36][37][38][39][40][41][42][43][44][45]. The prevalence of mental health symptoms exhibited great variations.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Another nine studies reported the prevalence of anxiety symptoms among HCWs [34, 35,36,39,[42][43][44][45], the prevalence was found to vary from 21.9%-73.5% [36,39]. Five studies investigated HCWs' perceived stress during the pandemic, between 15.5%-63.7% of HCWs reported high levels of work-related stress [34, 35,36,42,44].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations